PERSONALITY AND COGNITIVE FACTORS IN INFORMATION SYSTEM MIGRATION PROCESS - Willy Abdillah (Journal of Indonesian Economy and Business (JIEB), 2013)
This study predict potential resistance of IT adoption from perspective of cognitive and personality. Research conducted on 30 employees of PT. Berau Coal and 54 employees of PDAM Boyolali who are undergoing the process of migration of ERP and e-billing. Nonprobability sampling procedure was using in this research with purposive-judgment techniques. Primary data retrieved through a questionnaire with a closed question format. Hypothesis testing conducted using Partial Least Square with software applications 2.0.M3 version SmartPLS. The results show only the cognitive factors have positively influence on intention to adopt ERP and e-billing. This finding reinforces that the development of IT adoption theory will lead to perceptual factors. Also, this finding indicates that the employees of PT. Beraucoal and PDAM Boyolali have great intentions to use IT in term of ERP and ebilling migration process. Managerial implication and further researches are discussed.